(7x-8)(9x+8)=0

Simple and best practice solution for (7x-8)(9x+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (7x-8)(9x+8)=0 equation:


Simplifying
(7x + -8)(9x + 8) = 0

Reorder the terms:
(-8 + 7x)(9x + 8) = 0

Reorder the terms:
(-8 + 7x)(8 + 9x) = 0

Multiply (-8 + 7x) * (8 + 9x)
(-8(8 + 9x) + 7x * (8 + 9x)) = 0
((8 * -8 + 9x * -8) + 7x * (8 + 9x)) = 0
((-64 + -72x) + 7x * (8 + 9x)) = 0
(-64 + -72x + (8 * 7x + 9x * 7x)) = 0
(-64 + -72x + (56x + 63x2)) = 0

Combine like terms: -72x + 56x = -16x
(-64 + -16x + 63x2) = 0

Solving
-64 + -16x + 63x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-8 + -9x)(8 + -7x) = 0

Subproblem 1

Set the factor '(-8 + -9x)' equal to zero and attempt to solve: Simplifying -8 + -9x = 0 Solving -8 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -9x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -9x = 0 + 8 -9x = 0 + 8 Combine like terms: 0 + 8 = 8 -9x = 8 Divide each side by '-9'. x = -0.8888888889 Simplifying x = -0.8888888889

Subproblem 2

Set the factor '(8 + -7x)' equal to zero and attempt to solve: Simplifying 8 + -7x = 0 Solving 8 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -7x = 0 + -8 -7x = 0 + -8 Combine like terms: 0 + -8 = -8 -7x = -8 Divide each side by '-7'. x = 1.142857143 Simplifying x = 1.142857143

Solution

x = {-0.8888888889, 1.142857143}

See similar equations:

| 20x-5y=80 | | 5x-3y=80 | | 30=-3(n-7) | | -2n(2n-7)=0 | | -2=[-3+m]/8 | | 2x^4=10x^3 | | 360/4=x/12 | | -2x+5y=16 | | 5(x-8)/7=-7 | | -4x-4y=-24 | | 6x+3-2x=23 | | -2=(-3+m)/8 | | (-2)=x^3-2x | | 3x^2+x+1=2x-2 | | (-2)=x^3-2 | | 3y-13=18 | | 5x+25y=55 | | 3x+7(-x+4)=-2(x-5)+6x | | 5-2(2n-8)=-3(2n-5) | | -2=-3+m/8 | | 5x-25y=5 | | 78=6-6v | | -6+a/2=-8 | | 6(x+3)=6+8(x-1) | | X^2-x+0.05=0 | | 22+x+2=90 | | 4n+18=34whatisn | | (3a^2b)(-ab^2)= | | x/31=-20 | | 54=12x-(4x+10) | | 8(r-11)=3r | | 5x^2-18x+10=0 |

Equations solver categories